Screening and Identification of Hypoxia-Inducible Factor Signaling Inhibitor with Antiangiogenic Activity - Li, Chao; Wei, Yuanzheng; Wang, Ping; Xue, Xiaoxian; Wei, Guangyao; Chen, Mu; Zhang, Xinyun; Cai, Lei; Zhang, Yu; Zhang, Xumu; Li, Yingjun (Pharmaceutical Fronts, 2024)
Hypoxia-inducible factors (HIFs) play a key role in regulating cellular responses to low-oxygen conditions, particularly in promoting angiogenesis in tumor microenvironments. Aberrant HIF signaling enhances tumor growth and contributes to resistance against chemotherapy and radiotherapy. Targeting the HIF pathway has emerged as a promising strategy for cancer therapy. This study aimed to identify novel inhibitors of HIF signaling and evaluate their potential against the HIF–vascular endothelial growth factor (VEGF) axis for antiangiogenic therapy. In screening our in-house drug library using hypoxia response element dual-luciferase assay, HST3782, a novel 3-hydroxy-8-azabicyclo[3.2.1]octane-bridged compound, was identified as a promising HIF inhibitor, with IC50 of 1.028 μmol/L. In this work, the inhibitory effect of HST3782 on HIF signaling was confirmed in triple-negative breast cancer cells (SUM159) under hypoxic conditions (1% O2). Quantitative real-time polymerase chain reaction suggested the inhibitory effect of HST3782 on the expression of angiogenic genes, including VEGFa, VEGFR-1, BNIP3, and SERPINE1 in 786-O cells. Zebrafish model testing revealed that HST3782 inhibited intersegmental and subintestinal vessel development by up to 56% without marked toxicity. HST3782 was synthesized through a two-step 1,2,4 triazole cyclization reaction, followed by amide formation and ketone reduction steps. The last step of hydrogenation with sodium borohydride yielded a pair of endo-exo isomers. 2D-NOESY (Nuclear Overhauser effect spectroscopy) analysis confirmed that the compound's endo isomer (HST3782) had superior inhibitory effects relative to its exo form (8b). Given the above, HST3782 is a novel HIF inhibitor, with strong antiangiogenic effects and presents a valuable scaffold for future development of antiangiogenic drugs targeting the HIF–VEGF axis. Further studies are warranted to optimize HST3782's pharmacokinetics and therapeutic efficacy for antiangiogenic therapy in hypoxia-related malignancies.
Keywords: hypoxia-inducible factor; HIF pathway inhibitor; angiogenesis; zebrafish; bridged compound